2007
DOI: 10.1063/1.2727466
|View full text |Cite
|
Sign up to set email alerts
|

3-mercaptopropyltrimethoxysilane as insulating coating and surface for protein immobilization for piezoelectric microcantilever sensors

Abstract: We have examined coating (PbMg(13)Nb(23)O(3))(0.63)-(PbTiO(3))(0.37) (PMN-PT)/tin and lead zirconate titanate (PZT)/glass piezoelectric microcantilever sensor (PEMS) with 3-mercaptopropyl-trimethoxysilane (MPS) by a simple solution method to electrically insulate the PEMS for in-water applications. In contrast to earlier methytrimethoxysilane insulation coating, the MPS coating also facilitated receptor immobilization on the sensor surface via bonding of its sulhydryl group to a bifunctional linker, sulfosucci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 26 publications
2
58
0
Order By: Relevance
“…2 the in-air and in-water resonance spectra of a PZT/glass PEMS electrically insulated by a 3-mercaptopropyltrimethoxysilane ͑MPS͒ coating. 23 As can be seen from Fig. 2, the in-water resonance frequency and resonance peak width of the longitudinal mode and those of the width mode remained close to those of the in-air spectrum.…”
Section: A Sensor Arraysupporting
confidence: 49%
See 3 more Smart Citations
“…2 the in-air and in-water resonance spectra of a PZT/glass PEMS electrically insulated by a 3-mercaptopropyltrimethoxysilane ͑MPS͒ coating. 23 As can be seen from Fig. 2, the in-water resonance frequency and resonance peak width of the longitudinal mode and those of the width mode remained close to those of the in-air spectrum.…”
Section: A Sensor Arraysupporting
confidence: 49%
“…From our earlier studies, a typical saturation time ranges from a few minutes at higher concentrations, e.g., 10 5 spores/ ml to 15-30 min at lower concentrations, e.g., 10 1 spores/ ml. [20][21][22][23]26 The present detection scheme allowed us to detect BA over a wide range of concentrations, 10 1 -10 7 spores/ ml over a short time. While these experiments did not yield a linear dose response of the PEMS to these concentrations of BA, which would require preparing the sensor surface after detection at each concentration, they nonetheless amply demonstrated the "repeatability" of the detection from sensor to sensor, which is one of the main goals of this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct, label-free detection is achieved by monitoring the PEMS resonance frequency shift in real time. [8][9][10][11][12][13] In a previous study, we have demonstrated that 3-mercaptopropyltrimethoxysilane ͑MPS͒ can be used to coat a PEMS and serve both as an electrically insulating layer and as a substrate for immobilization of antibodies. The goal of this study was to investigate MPS-insulated PEMS for direct, rapid, label-free, in situ detection of Her2 at clinically relevant concentrations in mixed protein solutions.…”
Section: -13mentioning
confidence: 99%